If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7x-12)=(4x-17)
We move all terms to the left:
(7x-12)-((4x-17))=0
We get rid of parentheses
7x-((4x-17))-12=0
We calculate terms in parentheses: -((4x-17)), so:We get rid of parentheses
(4x-17)
We get rid of parentheses
4x-17
Back to the equation:
-(4x-17)
7x-4x+17-12=0
We add all the numbers together, and all the variables
3x+5=0
We move all terms containing x to the left, all other terms to the right
3x=-5
x=-5/3
x=-1+2/3
| 5(3×-2)-4=6x+2 | | 6-1/3x=1-1 | | 19=3z+4 | | 523+x=2052 | | -16x^2+26x+125=0 | | 10x+5=5x-13 | | (3x–5)=(4x–19) | | 13q+3q=-4q | | -7(r=8)=-14 | | 11-2d=7 | | 1=2x+1/× | | 4(y-6)-7y=6 | | 8-4(5)+16=x | | 0.11x=26+0.07x | | 2n+2/n=10 | | -x+3x=8 | | 7+3/5d=-5 | | y+2/3=7 | | 13q+3q=-4q= | | 0.4x+0.4x+(x-25)+110+(x-20)=540 | | -4m-7=1 | | 3+8=p | | 39=c3 | | 3(b-5)-2b=-12-3 | | b/11-4b/11=24/11 | | 10=8+n/4 | | 2x80=2×8× | | 13=n+14 | | 39=c•3 | | x+2.75=-0.25 | | 6(5y+7=7(4y-10) | | 8(-4x-6)=4x-12 |